CATASTROPHE THEORY AND ITS APPLICATION IN ECONOMICS - Hossein Abbasi Nejad; Shapour Mohamadi (فصلنامه پژوهش‌های اقتصادی ایران, 2002)
Sudden jumps, qualitative changes and discontinuities are not rare in social and economic phenomena. Catastrophe theory is a proper approach to modeling of dynamical systems that a company faces with sudden jump. Catastrophe theory can be applied in areas such as nonlinear growth models, technical changes, institutional changes, Philips curve, stock market, consumers' behavior and monopolistic behavior. This paper tends to clarify the theory and provide a general guideline to application of it in specific subjects.